2005
DOI: 10.1103/physrevlett.95.194501
|View full text |Cite
|
Sign up to set email alerts
|

Axisymmetric Bubble Pinch-Off at High Reynolds Numbers

Abstract: Analytical considerations and potential-flow numerical simulations of the pinch-off of bubbles at high Reynolds numbers reveal that the bubble minimum radius, rn, decreases as tau proportional to r2n sqrt[1lnr2n], where tau is the time to break up, when the local shape of the bubble near the singularity is symmetric. However, if the gas convective terms in the momentum equation become of the order of those of the liquid, the bubble shape is no longer symmetric and the evolution of the neck changes to a rn prop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

19
132
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 129 publications
(152 citation statements)
references
References 11 publications
19
132
0
1
Order By: Relevance
“…Other singularities [1] have been shown to be sensitive to noise [2]. However, experiment and theory up to now have ignored cylindrical asymmetry [21,22,23,24,25,26], or could not show it to be a generic feature of breakup [14]. We have shown that tilting the nozzle by just 0.07 • detectably alters the outcome of breakup.…”
mentioning
confidence: 80%
See 4 more Smart Citations
“…Other singularities [1] have been shown to be sensitive to noise [2]. However, experiment and theory up to now have ignored cylindrical asymmetry [21,22,23,24,25,26], or could not show it to be a generic feature of breakup [14]. We have shown that tilting the nozzle by just 0.07 • detectably alters the outcome of breakup.…”
mentioning
confidence: 80%
“…2) from a power law α h = 0.50 with logarithmic corrections (dotted lines) that have been derived for Eqn. 2 [14,24] -a limitation also encountered by Bergmann et al at low Froude numbers. However, these corrections are derived by assuming a slender cylinder, which we believe is a poor approximation to our neck shape.…”
mentioning
confidence: 93%
See 3 more Smart Citations